A new species Tetragono cephalum panjiensis N.Sp. (Eucestoda: Lecanicephalidae) from Trygon zugei at Panji, GoA, India - Khamkar*, D.D. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present paper deals with description of new species of genus Tetragonocephalum panjiensis n.sp. differs from all known species in length and breath of worm, size of scolex, number of testes, presence or absence of neck, shape and size of ovary and external seminal vesicle.